Trainee-Led Quality Improvement Project to Improve Fertility Preservation Counseling for Patients With Cancer. Issue 3 (March 2022) - Sena, Laura A.; Sedhom, Ramy; Scott, Susan; Kagan, Amanda; Marple, Andrew H.; Canzoniero, Jenna V.; Hsu, Melinda; Qasim Hussaini, Syed M.; Herati, Amin S.; Reschke, Lauren; Antero, Maria Facadio; Christianson, Mindy S.; et al.
Abstract : PURPOSE: Oncofertility counseling regarding the reproductive risks associated with cancer therapy is essential for quality cancer care. We aimed to increase the rate of oncofertility counseling for patients of reproductive age (18-40 years) with cancer who were initiating systemic therapy at the Johns Hopkins Cancer Center from a baseline rate of 37% (25 of 68, June 2019-January 2020) to 70% by February 2021. METHODS: We formed an interprofessional, multidisciplinary team as part of the ASCO Quality Training Program. We obtained data from the electronic medical record and verified data with patients by phone. We surveyed patients, oncologists, and fertility specialists to identify barriers. After considering a prioritization matrix, we implemented Plan-Do-Study-Act (PDSA) cycles. RESULTS: We identified the following improvement opportunities: (1) oncologist self-reported lack of knowledge about counseling and local fertility preservation options and (2) lack of a standardized referral mechanism to fertility services. During the first PDSA cycle (February 2020-August 2020, disrupted by COVID-19), we introduced the initiative to increase oncofertility counseling at faculty meetings. From September 2020 to November 2020, we implemented a second PDSA cycle: (1) educating and presenting the initiative at Oncology Grand Rounds, (2) distributing informative pamphlets to oncologists and patients, and (3) implementing an electronic medical record order set. In the third PDSA cycle (December 2020-February 2021), we redesigned the order set to add information (eg, contact information for fertility coordinator) to the patient after-visit summary. Postimplementation (September 2020-February 2021), counseling rates increased from 37% to 81% (38 of 47). CONCLUSION: We demonstrate how a trainee-led, patient-centered initiative improved oncofertility care. Ongoing work focuses on ensuring sustainability and assessing the quality of counseling.